2013
DOI: 10.1007/s13320-013-0122-7
|View full text |Cite
|
Sign up to set email alerts
|

Derrick safety monitoring system based on fiber Bragg grating strain sensors

Abstract: The fiber Bragg grating (FBG) strain sensor is used in the oil and gas derricks for the health monitoring. The system consisted of the FBG strain sensors, optical interrogator and monitoring software. 64 sensors were installed on a derrick for loading and unloading tests. The results showed that the monitoring system had the advantages of the high accuracy, good repeatability, large capacity and real-time monitoring ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…While these embedded optical fibre sensors can give access to unique information inside a structure, they cannot be repaired or replaced if needed. In another way, Guo et al [12] and Cheng et al [13] proposed packaged structure FBG sensors, suitable for local surface strain measurements. Although these packaged sensors are reusable, and exhibit enhanced strain sensitivities compared to bare FBGs, their complex design and size-10 cm long for the one developed by Guo et al [12]-are not suitable for all applications.…”
Section: Introductionmentioning
confidence: 99%
“…While these embedded optical fibre sensors can give access to unique information inside a structure, they cannot be repaired or replaced if needed. In another way, Guo et al [12] and Cheng et al [13] proposed packaged structure FBG sensors, suitable for local surface strain measurements. Although these packaged sensors are reusable, and exhibit enhanced strain sensitivities compared to bare FBGs, their complex design and size-10 cm long for the one developed by Guo et al [12]-are not suitable for all applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wang (2010) [12] used distributed data acquisition system, set up an experimental device, and achieved the detection of the drilling rig working condition parameters and feedback control. Cheng et al (2013) [13] used the fiber Bragg grating (FBG) strain sensor in oil and gas derricks for health monitoring and found that the monitoring system had the advantages of high accuracy, good repeatability, large capacity, and realtime monitoring ability. Deng and Chang (2013) [14] analyzed the anti-jamming performance of the top drive control system and gave the corresponding solution to the interference.…”
mentioning
confidence: 99%